1997
DOI: 10.1515/jbcpp.1997.8.1-2.31
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Antioxidant Vitamins on Red Blood Cell Lipoperoxidation induced by SO2 inhalation

Abstract: The aim of this research was to determine whether administration of antioxidant vitamins can reduce oxidant damage in erythrocytes induced by sulfur dioxide (SO2) inhalation. Meth- and sulfhemoglobin ratios, malonyldialdehyde (MDA) levels, osmotic fragility ratios and hematological parameters of a total of 28 rats were compared. SO2 was given at 10 ppm, 1 hour daily, for 45 days in a specially designed chamber. DL-alpha-Tocopherol acetate (40 mg/kg) and Na-ascorbate (200 mg/kg) treatments, initiated 3 days bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…The effect of SO 2 on the antioxidant status and lipid peroxidation of red blood cells and their reactions to ingested, inhaled, and parenterally administered sulfite have been described (Etlik et al 1997;Jenkins et al 2000). Inhalation of SO 2 causes bronchoconstriction (Lazarus et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of SO 2 on the antioxidant status and lipid peroxidation of red blood cells and their reactions to ingested, inhaled, and parenterally administered sulfite have been described (Etlik et al 1997;Jenkins et al 2000). Inhalation of SO 2 causes bronchoconstriction (Lazarus et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C (ascorbic acid) administration before transportation protected the erythrocyte membrane in pigs (Adenkola et al, 2010a, Adenkola et al, 2010b and goats (Minka & Ayo, 2010) transported by road for several hours. Vitamins C and E supplementation also reduced erythrocyte osmotic fragility and oxidative damage in rats (Etlik et al, 1997;Kraus et al, 1997) and chickens (Azeez et al, 2011a). In Gezel and Makoei breeds of sheep, increased vitamin E (α-tocopherol) levels associated with the increase in age caused a decrease in erythrocyte osmotic fragility (Asri-Rezaei et al, 2006).…”
Section: Nutritionmentioning
confidence: 99%
“…Increased MDA levels were also shown in rats experimentally exposed to SO 2 inhalation. Etlik et al [1997] found significant decrease in MDA levels in rats which were pretreated with antioxidant vitamins. The occurrence of lipid peroxidation, therefore, may be considered as a new mechanism causing bronchoconstriction via changing membrane properties of bronchial smooth muscles or other cells in the airways of WIAS.…”
Section: Discussionmentioning
confidence: 86%